2020
DOI: 10.1108/jhom-08-2019-0234
|View full text |Cite
|
Sign up to set email alerts
|

Social media hospital ratings and HCAHPS survey scores

Abstract: PurposeTo empirically verify whether patient hospital satisfaction ratings on social media such as Yelp provide similar information as the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) surveys.Design/methodology/approachOLS and ordinal regressions performed on secondary data obtained from Yelp.com and 2016 Hospital Compare database disclosed by CMS.FindingsResults show that the patient hospital satisfaction ratings from Yelp can predict the patient experience of care domain scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Several studies indicated that online review and social media research possess greater scientific value to explore. Few research works have examined the relationship between online review sites and hospital quality indicators [ 12 , 13 ] or conventional patient satisfaction surveys [ 6 , 14 ]. Meanwhile, other researchers examined the quality of online reviews in relation to public perceptions and sentiments [ 2 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that online review and social media research possess greater scientific value to explore. Few research works have examined the relationship between online review sites and hospital quality indicators [ 12 , 13 ] or conventional patient satisfaction surveys [ 6 , 14 ]. Meanwhile, other researchers examined the quality of online reviews in relation to public perceptions and sentiments [ 2 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, further studies are necessary to ascertain the connection between patient online reviews and other hospital quality measures. For example, evaluating the relationship between quality dimensions derived from social media reviews and patient satisfaction as measured by prior studies [ 35 , 70 ]. In addition, a comparison of the labeled dataset used in this study to other dictionaries or tools used in prior studies to enhance sentiment and text classification would be beneficial [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The digital consumer movement on social media influenced patient autonomy and self-determination in medical treatment, highlighting the essential importance of online patient experience in determining health care quality [ 3 , 34 ]. While many studies have examined the use of social media in hospital settings, the bulk of them examines the use of Twitter or Yelp as a social media tool for evaluating the quality of hospital services, rather than the Facebook platform [ 11 , 12 , 17 , 35 ]. This is very certainly due to a population’s preference for social media in various countries.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Technological innovation is essential for creating new ways for rapidly assessing the quality of services at an affordable cost. Therefore, social media platforms, which are often referred to as patient online reviews (POR), have been suggested as a new way for gauging patient satisfaction and monitoring treatment quality [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Additional study on the patient viewpoint and its relationship to hospital patients' total Facebook ratings discovered associations with a variety of issues, including wait times, treatment effectiveness, and communication [28]. With an increasing number of patients asking and freely sharing hospital evaluations on social media, feedback data may supplement conventional patient satisfaction surveys [14,27].…”
Section: Introductionmentioning
confidence: 99%